Numerical investigation on a heat-driven free-piston thermoacoustic-Stirling refrigeration system with a unique configuration for recovering low-to-medium grade waste heat. (October 2021) - Luo, Kaiqi; Zhang, Limin; Hu, Jianying; Luo, Ercang; Wu, Zhanghua; Sun, Yanlei; Zhou, Yuan
Highlights: A novel heat-driven free-piston thermoacoustic Stirling cooling system is proposed. The direct-coupling and single displacer configuration is introduced in the system. The influences of various operating conditions are systematically analyzed. It can achieve a COP above 0.60 below a heating temperature of 300°C. Abstract: In this paper, a unique heat-driven free-piston thermoacoustic-Stirling refrigeration configuration is proposed to effectively provide room-temperature cooling by using low/medium-grade waste heat. Compared with the traditional duplex free-piston Stirling refrigerator, the unique feature of the proposed novel configuration is that it has only one single moving displacer and uses a thermal buffer tube to directly couple a thermoacoustic heat engine and a refrigerator, consequently leading to higher reliability and compactness. Numerical simulation and analysis have been conducted, focusing on the acoustical and thermodynamic characteristics as well as its global cooling performance. The thermoacoustic characteristics of the system are analyzed in details to understand its operating mechanism and cooling performance. Additional analyses are focused on the influences of the heating temperature and the working pressure on the thermodynamic performances of this system. A 2kW-class case study for air-conditioning refrigeration application shows that it can achieve a COP (coefficient of performance) of more than 0.62 at a refrigeration temperature of 10°C, under the conditions of an ambient temperature of 50°C and a heating temperature of 300°C. Its compactness and high efficiency are very competitive to the current heat-driven refrigerators, showing great potential in compact air-conditioning application by utilizing low-to-medium grade waste heat sources.